2021
DOI: 10.21203/rs.3.rs-136045/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anti-Inflammatory Diet Consumption Reduced Fatty Liver Indices: Finding From A Large Cohort Study in the Kurdish Population

Abstract: The aim of this study was the assess association between of dietary inflammatory index (DII) and non-invasive markers of liver status in adults. This cross-sectional study was performed on 8,520 adults, recruited in Ravansar Non-Communicable Diseases (RaNCD) cohort study, the west of Iran. DII score was calculated based on participants’ dietary intakes obtained from Food Frequency Questionnaire (FFQ). Fatty Liver Index (FLI) score was calculated by anthropometric measurements and some non-invasive markers of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…In the AID group, there was a significant decrease in ALP levels. Darbandi et al (2020) have shown that adherence to an AID is associated with lower liver enzymes, including AST, ALT, and GGT. It seems that weight loss inhibits the accumulation of lipid in hepatocytes, resulting in a reduction of inflammatory response via NF‐κB activation and cytokine production, which leads to a decrease in liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…In the AID group, there was a significant decrease in ALP levels. Darbandi et al (2020) have shown that adherence to an AID is associated with lower liver enzymes, including AST, ALT, and GGT. It seems that weight loss inhibits the accumulation of lipid in hepatocytes, resulting in a reduction of inflammatory response via NF‐κB activation and cytokine production, which leads to a decrease in liver damage.…”
Section: Discussionmentioning
confidence: 99%